#TITLE_ALTERNATIVE# - RAHMAH (NIM 10107088); Pembimbing : Prof. Dr. Sutawanir Darwis, AULIA
Permeability is one of the characteristics of the rock that is able to drain the fluid through the pores. The increasing of permeability in the reservoir also resulted in increased flow rate of fluid. Optimization of a reservoir can be done by estimating the parameter of permeability. In predicting the permeability parameters needed a method that can update the permeability parameters continuously. Ensemble Kalman Filter (EnKF) is a method that can perform parameters updating of reservoir sequentially by using analytical or numerical solutions for non-linear model. To obtain the solution from some equation is not always easy to be solved analytically. Therefore, we need a solution numerically to ease in obtaining the solution of an equation. In this final project, EnKF method is used to estimate the permeability from data dynamic of pressure for infinite reservoir using the diffusivity equation numerical solutions that is obtained by the Gaver-Stehfest algorithm. Furthermore, the results that obtained numerically are compared with results that obtained analytically to see consistency between the numerical and analytical results.